ANALYSIS OF THE EFFECTIVENESS OF MONETARY POLICY IN CONTROLLING INFLATION IN INDONESIA - Simbolon, Nurhawani; Rusiadi, Rusiadi; Nasution, Lia Nazliana (PT. Arsil Reka Engineering, 2024)
This study aims to analyze the effectiveness of monetary policy in controlling inflation in Indonesia. It uses variables such as inflation, money supply, economic growth, interest rates, exchange rates, and the consumer price index. The data analysis model in this study uses Vector Autoregression (VAR), as seen from the Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) analyses. This study uses secondary data from 2000 to 2023. The VAR results show that in the short, medium, and long term, inflation has a significant effect on the consumer price index in the short, medium, and long term. The money supply in the short term is influenced by the consumer price index, while in the medium and long term, the money supply is influenced by inflation.